2022
DOI: 10.3390/antiox11081572
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Enriched Spirulina (SeE-SP) Enhance Antioxidant Response, Immunity, and Disease Resistance in Juvenile Asian Seabass, Lates calcarifer

Abstract: The present study examined the efficacy of dietary selenium-enriched spirulina (SeE-SP) on growth performance, antioxidant response, liver and intestinal health, immunity and disease resistance of Asian seabass, Lates calcarifer. A total of 480 seabass juveniles with an initial weight of 9.22 ± 0.09 g/fish were randomly assigned to four dietary groups. The fish were fed a fishmeal protein replacement diets with SeE-SP at 5%, 10%, and 20%, namely SeE-SP5, SeE-SP10, and SeE-SP20, and a fishmeal-based diet as con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
(77 reference statements)
1
11
0
Order By: Relevance
“…Similar results regarding GPx, CAT, and SOD activities in liver tissues of loach were reported by Hao, [33]. In addition, several studies on different fish species evaluated different Se sources and mostly reported that Se supplementation strengthens the antioxidant system by improving GPx activities [12,28]. However, TBARS values were not changed across the treatments in our experiment.…”
Section: Plos Onesupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results regarding GPx, CAT, and SOD activities in liver tissues of loach were reported by Hao, [33]. In addition, several studies on different fish species evaluated different Se sources and mostly reported that Se supplementation strengthens the antioxidant system by improving GPx activities [12,28]. However, TBARS values were not changed across the treatments in our experiment.…”
Section: Plos Onesupporting
confidence: 90%
“…Selenium is the key trace element required to smooth the growth and metabolism of animals including fish [8]. Research is established in different animal species that dietary Se deficiency led to lower growth performance, exudative diathesis, nutritional muscular dystrophy, and reproductive issues in different animal species [9][10][11][12][13]. The Se toxicity due to higher dosage led to digestive upset and down-regulation of the immune system of the fish [14].…”
Section: Introductionmentioning
confidence: 99%
“…Pacific white shrimp ( L. vannamei ) postlarvae fed a diet containing 0.75% T. suecica resulted in a 30% greater weight increase compared to larvae fed diets without it 184 . Similarly, Arthrospira as a FM replacer could improve the growth performance of various fish species such as juvenile Asian seabass, Lates calcarifer ; Nile tilapia, Oreochromis niloticus ; Golden barb, Puntius gelius and tilapia, Oreochromis aureus × Oreochromis mossambicus , at inclusion levels in the range 10%–30% 32,159,186–188 . Growth in Senegalese sole ( Solea senegalensis ) juveniles was substantially improved (84%–97%) with a freeze‐dried microalgae biomass diet comprising Tisochrysis lutea and N. gaditana in comparison to the control diet formulated without the inclusion of microalgae 189 .…”
Section: The Role Of Microalgae In Aquaculture Productionmentioning
confidence: 99%
“…A number of studies have shown that a reasonable inclusion of microalgae in fish diets increased feed intake in fish. However, inclusion rates of more than 10% microalgae may have a negative impact on the feed conversion ratio (FCR) and feed intake 32,185 . High algae inclusion (30% in the feed) resulted in lower feed intake with the poorest FCR in Atlantic cod, G. morhua ; most likely due to issues with feed palatability 172 .…”
Section: The Role Of Microalgae In Aquaculture Productionmentioning
confidence: 99%
See 1 more Smart Citation